Istirātījīyāt Taʿlīm ʿAnāshir al-Lughah wa-al-Mahārāt al-Lughawīyah al-ʿArabīyah - Alwani Alwani (Alsina : Journal of Arabic Studies, 2021)
Arabic is the language of the Qur'an and is one of the languages of international communication. Learning Arabic is a must for everyone, especially Muslims, but over time many have experienced difficulties in learning Arabic because the material in Arabic is so complex and abundant that teachers need strategies in teaching Arabic. Learning requires the use of learning strategies so that students do not find it difficult. The application of Arabic learning strategies is so that students can receive the material more effectively. The choice of strategy should be based on the language skills taught to students. This research aims to analyze strategies of learning Arabic elements and Arabic skills. The research method is library research which is some of the data resources took by books and journals; then researcher analyze the data with content analysis methods. In designing learning strategies, several components must be considered, namely preliminary learning activities, delivery of information, student participation, test activities, and follow-up activities. There are six types of Arabic learning strategies based on language skills, namely vocabulary learning strategies, grammar learning strategies, listening learning strategies, speaking learning strategies, reading learning strategies, and writing learning strategies.